Redefining weed control: Effective strategies for finger millet (Eleusine coracana) - Anupriya , S; Sivakumar , C; Anitta, F S; Thirukumaran , K; Sivakumar , R; Ragunath , K P; Pazhanivelan , S (Plant Science Today, 2025)
Being a significant rainfed crop with high nutritional value, finger millet experiences a decrease in both growth and productivity due to various biotic and abiotic stresses. One important biotic stress element negatively affecting finger millet yield is weed infestation. The crop's delayed initial growth increases its susceptibility to weed infestation and increases competition for resources. Echinochloa colona (Jungle rice), Cyanadon dactylon (Bermuda grass), Eleusine indica (Indian goosegrass), Cyperus rotundus (Purple nutsedge), Digitaria sangunalis (Crabgrass) and Commelina benghalensis (Bengal dayflower) are among the prominent weed species found in finger millet cultivated lands. Effective weed control is crucial for enhancing farmers' yield and income. Various weed control strategies mitigate weed competition, including mechanical, cultural, chemical and integrated approaches. Among these, Integrated Weed Management (IWM), which combines cultural, mechanical and judicious use of herbicides, has shown promising results in enhancing weed suppression while maintaining soil health and sustainability. This review consolidates findings from recent studies and field trials to provide a comprehensive guide on weed management strategies in finger millet, aiming to improve productivity and promote environmentally sustainable practices.